Improving Students’ Comprehension on Descriptive Text by Using Graphic Organizers Integrated with Islamic Values - Siregar, Nurhafni; Sari, Dwi Novita; Fitria, Dewi; Yarshal, Dinda; Lestari, Nila; Hasanah, Hasanah; Nurmairina, Nurmairina (Universitas Muhammadiyah Sumatera Utara (UMSU), 2026)
The purpose of this study was to find out whether the use of graphic organizers integrated with Islamic values can improve students’ ability to comprehend descriptive texts. Since the true education requires a balance of cognitive development and character development or moral fortitude as the world becomes far from religious path, therefore, this study carried Islamic values as part of classroom English. The subject of this research was grade eight of SMPIT Al-Fauzi Medan of 2023/2024 academic year which consists of 25 students. Classroom action research was implemented following Kurt Lewin's model with action research procedures, namely planning, implementation, observation, and reflection. This research was conducted in two cycles in each cycle consists of two meetings. Data collection techniques in this study used the following instruments: interviews, field notes, questionnaires, and tests. The results of this study integration of media GO with Islamic values showed significant improvement on students' comprehension on descriptive texts. Students achieve expected grades which is higher than the minimum criteria 70 gradually at the end of the cycle. The average score of the students on the initial test was 51.25. The average value of students in the first cycle is 58.75. The average value of students in the second cycle is 72.80. Hence, there are positive responses from students and English teachers regarding to the use of media graphic organizers integrated with Islamic values to improve students’ comprehension on descriptive text.